New method for warp yarn arrangement and algorithm for pattern conversion for three-dimensional woven multilayered fabrics. (June 2020) - Vorhof, Michael; Weise, Daniel; Sennewald, Cornelia; Hoffmann, Gerald
Three-dimensional fabrics have an enormous potential for the manufacturing of semi-finished products in a direct preforming procedure for fiber-reinforced materials. The production of these three-dimensional fabrics involves the processing of coarse reinforcing yarns with high warp density. However, conventional weaving looms have not been designed for such applications, and their maximal achievable warp yarn density is therefore severely limited. Friction and clamping between warp yarns impede the shedding process, and fragments of damaged or fibrillated fibers interfere with the weaving process. Most of the solutions for these issues, which has been presented so far, are based on noncommercial technologies or require extensive modification on standard weaving machines. Hence this paper proposes a new shedding method based on double flat steel heddles, which is suitable for the use in conventional weaving looms. The paper gives a detailed description of the new shedding method including the required materials and the technological framework. Furthermore, a suitable algorithm for the fast pattern conversion under consideration of the special technological framework and requirements of the shedding is presented.